Meniace sa trendy výskumu minulosti populácie na Slovensku - Ján Golian (AntropoWebzin, 2012)
Works dealing with the issue of population research in Slovakia, a field which significantly developed during the second half of the 20th century, have often built on the earlier works of the interwar period. The common denominator of these works was most frequently the current issue of ethnicity and the need felt by Slovaks to demarcate their borders (especially the Southern border) in a young Czechoslovakia (A. L. Petrov, J. Husek). Academic grappling with present demographic questions reagrding interwar Slovakia (A. J. Chura, J. Svetoň) resumed after the Second World War, with new questions regarding the demographic developments in Upper Hungary from the 18th century onwards. The School of modern historical demography which has its roots in French academia did not, unfortunately, establish itself in Slovak academia. The few works published (J. Alberty, M. Kohútová, J. Kandert) failed to elicit the necessary inspiration and no increase was noted in graduate dissertations produced on these topics at Slovak universities.Today, in the era of free historical inquiry, P. Tišliar‘s and B. Šprocha‘s accounts of population history research reach new audiences. Similarly, our thesis “ Social and Confessional Determinants of Demographic Development in the Podpol’ania in a “long” 19th Century” aims to contribute to these modern works and open a discussion on historical demography in the specific micro region of Detva.